Pemanfaatan Electronic Banking Bagi Anggota di KSPPS BMT Bina Ummat Sejahtera Cabang Tayu - Husna, Farida Fadlliatul; Mustaqim, Muhamad (IAIN Kudus, 2020)
This paper aims to examine the utilization of electronic banking for members in KSPPS BMT Bina Ummat Sejahtera (BUS) Tayu Branch, as well as the factors that influence it. This research is included in field research with qualitative approach. The results showed that the utilization of electronic banking in BMT Bina Ummat Sejahtera is currently not fully carried out. Some members still do not use electronic banking, for several reasons such as: limited facilities, perceptiveness about e-banking that impresses, complicated, and worries about security risks. Meanwhile, factors that influence the utilization of e-banking include: member interest, desire to use, perception that includes: perception of trust, ease, and risk perception. The results of this study provide an idea that it is necessary to socialize and educate the use of e-banking, especially for the lower middle class, and rural areas.